LibraPal: Read with Lexi & Lumi - Marwa Rashwan (21678207) (2025)
LibraPal: Read with Lexi & Lumi is an AI-powered reading companion designed to enhance student engagement with books. By integrating gamification, personalized recommendations and AI-generated video recaps, LibraPal makes reading more interactive and enjoyable. Students can log their progress, compete in challenges, and share their learning in a dynamic way. The platform fosters a love for reading by collaborating with libraries and schools to provide a supportive and motivating environment. Learn more about LibraPal at https://librapal.njaz.org/. Other Information Poster was presented at: Libraries Thriving Together in an Open Ecosystem https://www.qnl.qa/en/libraries-lead-forum-2025 License: https://creativecommons.org/licenses/by/4.0/ Conference information: Libraries Lead Forum 2025 https://www.qnl.qa/en/libraries-lead-forum-2025/agenda